Strategi Pembelajaran Matematika Mengenal Nilai dan Angka Melalui Bermain dan Benda-Benda Konkret pada Anak Usia Dini - Amalia Husna; Nurhafizah Nurhafizah (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
Mathematics is one of the cognitive aspects that must be introduced to children at an early age to achieve a standard of cognitive development called the Child Development Achievement Level Standard (STPPA) as stated in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 137 of 2014. One of the basic learning Mathematics is a child recognizes the concept of numbers and understands numbers. So that children's understanding is in accordance with the concept, children must learn mathematics from concrete objects and by playing. the introduction of values ​​and numbers in children aged 2-8 years children need concrete objects, because at this age, children recognize concepts using symbols. This study aims to find a strategy for learning mathematics to recognize values ​​and numbers through play and concrete objects in early childhood. This type of research is descriptive qualitative with literature study method. As for the results of the research, the strategies that can be used in introducing children to numbers through play and concrete objects are: (1) Singing; (2) Flannel Board Media; (3) Calendar Games; (4) Number Card; (5) Counting Things in Daily Life; (6) Dice; (7) Write Numbers (8) Number Fishing Media; (9) Snakes and Ladders Game; (10); Congklak Game; (11) Finger Method.